Pilot study of the efficacy of eye movement desensitization and reprocessing (EMDR) intervention for injured division I student-athletes - Trenhaile, J; Trenhaile, T; Munce, T. (The Sport Journal, 2025)
Four NCAA Division I student-athletes, who had previously been injured, volunteered to participate in Eye Movement Desensitization and Reprocessing therapy (EMDR) and completed both pre and post test measures. The sessions ranged from five to eight treatments and results on the Profile of Mood States 2nd Edition - Adult Short (POMS 2-A Short) indicated notable decreases on Total Mood Disturbance and Tension/Anxiety scales. Increases were found on the Vigor/Activity scale (Positive Mood State). The student-athletes who participated in the study achieved "personal records" in 11 of the 17 potential areas of measure for a "personal record" in their sport. In addition, some student-athletes achieved multiple "personal records" in some of their events. Utilizing EMDR therapy with student-athletes who are experiencing distress or declining performance should receive notable consideration by mental health clinicians who are providing therapeutic services to collegiate student-athletes.